Different vantage points amongst different stakeholders in NATECH (NAtural hazard-triggered TECHnological) disasters: A case from the 2018 Mt. Anak Krakatau eruption and tsunami. Issue 1 (January 2021) - Pelupessy, Dicky; Jibiki, Yasuhito; Lestari, Fatma; Zulys, Agustino; Imamura, Fumihiko
Abstract: Previous literature on natech (Natural hazard-triggered TECHnological) disasters argue prevailing difficulties in establishing collective response and sharing common knowledge amongst different and a variety of stakeholders. We aim to describe such challenges using a case study and examine the relationship amongst the actors. Our case study focused on the 2018 Mt. Anak Krakatau eruption and the tsunami triggered by it. In this disaster, one of the largest industrial zones in Indonesia was partially affected. Our study largely explains the results based on some series of discussions with private companies and representatives of the residents collected in 2019 (from February to July). We also referred to the publicly available information, which relevant agencies in the Government of Indonesia issued. Although there were no physical damages in the factories and no causalities, staff in many facilities were worried about the situation and the surrounding residents were also scared how things would be going. The residents were not able to behave in collectively organized manner, because they faced with a lack of the synthesized and coordinated information and instructions. The residents were fully aware of the risk of natech disaster, but such awareness was not necessarily connected with reasonable risk perception and organized behaviours. Relevant organizations complied with their own protocols, but it did not necessarily bring better consequences. The meteorological agency disseminated information in their limited capacity. The volcano monitoring agency paid the limited focus on the volcano and its adjacent sea area. The national and local disaster management agencies tried to integrate technical information, but it took time. The companies carefully gathered information, but their priorities initially went to their internal response, including taking care of the families of their employees. These findings indicate that efforts were done in the right course separately and it is hard to achieve harmonized response under great uncertainty during a crisis.